1982
DOI: 10.3133/ofr82994
|View full text |Cite
|
Sign up to set email alerts
|

Shallow subsurface temperatures and some estimates of heat flow from the Colorado Plateau of northeastern Arizona

Abstract: Temperature data to depths of a few hundred meters were obtained from 29 wells in northeastern Arizona; in the region surrounding the San Francisco Volcanic Field, 8 in the Black Mesa area, and 9 in the south-central Colorado Plateau which includes the White Mountains. Although there was evidence for local hydrologic disturbances in many temperature profiles, most wells provided an estimate of the conductive thermal gradient at the site. A few thermal conductivities were measured and were combined with publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In fact, the estimated temperatures are high enough to consider the SFVF anomalously hot in comparison to average continental crust. Moreover, while at first glance it may seem that the relatively lower surface heat flow values measured in this region (likely associated with groundwater flow, Paul Morgan et al, ; Shearer & Reiter, ; Sass et al, ) are controlling our results, this is not the case, as this observable puts only mild constraints on the final thermal structure in comparison to seismic and geoid data. In this context, it has been shown that the effect of compositional heterogeneities on temperature structure within the crust may result in variations of ≥100 °C at middle crustal depths over short distances (Furlong & Chapman, ).…”
Section: Main Results and Discussionmentioning
confidence: 64%
“…In fact, the estimated temperatures are high enough to consider the SFVF anomalously hot in comparison to average continental crust. Moreover, while at first glance it may seem that the relatively lower surface heat flow values measured in this region (likely associated with groundwater flow, Paul Morgan et al, ; Shearer & Reiter, ; Sass et al, ) are controlling our results, this is not the case, as this observable puts only mild constraints on the final thermal structure in comparison to seismic and geoid data. In this context, it has been shown that the effect of compositional heterogeneities on temperature structure within the crust may result in variations of ≥100 °C at middle crustal depths over short distances (Furlong & Chapman, ).…”
Section: Main Results and Discussionmentioning
confidence: 64%
“…We emphasize, however, that these relative low temperatures in the SFVF area do not strictly correspond to a ''cold'' crustal region; temperatures beneath the SFVF (especially at mid/lower crustal depths) are still high enough to be considered anomalously high in comparison to average continental crust. Moreover, while at first glance it may seem that the low surface heat flow measured in this region (likely associated with groundwater flow [Morgan et al, 2004;Sass et al, 1982;Shearer and Reiter, 1981]) is controlling our results, this is not the case, as this observable put only mild constrains to the final thermal structure in comparison to seismic and geoid data. (Figures 9, 10, 12, and S10) are indicated by dashed lines.…”
Section: Temperature Structurementioning
confidence: 72%